2017
DOI: 10.1080/13621718.2017.1302180
|View full text |Cite
|
Sign up to set email alerts
|

Transient liquid phase bonding of 304 stainless steel using a Co-based interlayer

Abstract: Transient liquid phase bonding of AISI 304 austenitic stainless steel was carried out using a Co-based interlayer with 40 μm thickness. The effect of bonding time and solid-state homogenisation time on the microstructure and mechanical properties of samples was investigated. The results showed that isothermal solidification was completed within 30 min at a constant temperature of 1180°C. With increasing homogenisation time, at 1000°C, a more uniform distribution of alloying elements and hardness profile across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…As a result the width of ISZ widened as the diffusion of the MPD element grows. This observation is in line with other studies [15,28,29]. The DAZ which composed of second-phase precipitates distributed in the BM was formed as a result of solid-state diffusion and segregation of interlayer elements into the BM.…”
Section: Effect Of Bonding Time On Joint Microstructuresupporting
confidence: 93%
“…As a result the width of ISZ widened as the diffusion of the MPD element grows. This observation is in line with other studies [15,28,29]. The DAZ which composed of second-phase precipitates distributed in the BM was formed as a result of solid-state diffusion and segregation of interlayer elements into the BM.…”
Section: Effect Of Bonding Time On Joint Microstructuresupporting
confidence: 93%
“…In another work of the same research group from Sharif University of Technology [105] that used the same bonding conditions and discusses the corrosion behavior of these joints, even 83% of the base materials strength could be accomplished. The research group further reported on shear strength of diffusion bonded (1150 • C, 30 min, 0.2 MPa) 304 stainless steel plates using a 40 µm Co-based interlayer [106]. With this set-up a shear strength of up to 90% of the base material was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The research proposed here is a novel multi-scale lattice structure manufacturing platform that will utilize the dip-coating science for delivering the interlayer particles in hard to reach places and liquid-bridge the gap for TLP bonding. Since its invention in the early 1970s, much work has been performed on optimizing TLP bonding parameters, a list that includes temperature, holding time 74 , pressure, base materials 75 , interlayer composition 76,77 , MPD types, diffusion rate 78 , and microstructure development 79,80 . However, faying surfaces are commonly assumed to be semi-infinite flat substrates and the interlayer material is generally applied in the form of thin foil [81][82][83] , fine powder (with or without binder) 84,85 , paste 86 , electroplate 87,88 and, sputter 89,90 .…”
Section: Discussionmentioning
confidence: 99%